Pengaruh Riview Melalui Perceived Quality, Price Terhadap Purchase Order Studi Kasus Konsumen Kosmetik (Produk Skintific) di Kecamatan Johan Pahlawan - Salsabila Salsabila; Ivon Jalil; Cut Mega Putri (Indo Publishing, 2026)
This study aims to analyze the effect of reviews through perceived quality and price on purchase orders among Skintific cosmetic consumers in Johan Pahlawan District. The research is motivated by the growing influence of consumer reviews in shaping perceptions and purchase decisions, especially among young consumers who are active on social media. This study employs a quantitative research method with an associative approach. The population consists of all Skintific consumers in Johan Pahlawan District, with a sample of 100 respondents selected through a survey using a Likert-scale questionnaire. Data were analyzed using SPSS version 27.0, including validity and reliability tests, classical assumption tests, path analysis, and the Sobel test to examine mediation effects. The results show that reviews have a positive and significant effect on perceived quality, price, and purchase orders. Furthermore, both perceived quality and price have positive and significant effects on purchase orders. The mediation test results indicate that perceived quality and price partially mediate the relationship between reviews and purchase orders. Therefore, consumer reviews play a crucial role in enhancing quality perception, price evaluation, and purchase decisions regarding Skintific cosmetic products.